Digital Twin-Driven Intelligent Collaborative Automation Model for Global Warehouse Networks and Application Validation - Ni, Dingsong (Innovation in Science and Technology, 2025)
In the context of accelerated globalization, multinational logistics companies are confronted with significant challenges in global warehousing networks, including information latency, resource misallocation, and inefficient collaboration. This study addresses these issues by introducing digital twin technology to construct a virtual mirroring system for the overseas warehouse layouts of DongGuan Kreen Import and Export Co., Ltd. (with branches in the United States, Canada, Germany, and Vietnam). The digital twin system enables real-time collaboration and automated scheduling across global warehousing nodes, thereby enhancing the resilience of the global supply chain. The research is centered on three main aspects: First, a dynamic digital twin model is developed based on the physical space, equipment status, and business data of global warehousing nodes, achieving millisecond-level synchronization between physical and virtual warehouses. Second, intelligent resource allocation algorithms, automated cross-continental transfer decision mechanisms, and autonomous abnormal event response processes are designed to upgrade warehouse collaboration from a “passive execution” to an “active prediction” mode. Third, the digital twin model is validated in the context of “Amazon FBA headhaul logistics,” focusing on its collaborative efficiency in global warehouse stocking, replenishment, and return/exchange processes, with an emphasis on improving the response speed of cross-border e-commerce supply chains. The study demonstrates that the digital twin-driven intelligent collaborative automation model for global warehouse networks significantly enhances collaborative efficiency and supply chain resilience, forming a technical standard and practical paradigm for digital twin automation collaboration in global warehouses. This provides technological support for multinational logistics companies to address global warehousing collaboration challenges and enhances China’s scheduling discourse power in the global supply chain.